A pilot study of disparity vergence and near dissociated phoria in convergence insufficiency patients before vs. after vergence therapy - Alvarez, Tara L. (Frontiers in Human Neuroscience, 2015)
Purpose: This study examined the relationship between the near dissociated phoria and disparity vergence eye movements. Convergence insufficiency (CI) patients before vergence therapy were compared to: (1) the same patients after vergence therapy; and (2) binocularly normal controls (BNC). Methods: Sixteen subjects were studied—twelve BNC and four with CI. Measurements from the CI subjects were obtained before and after 18 h of vergence eye movement therapy. The near dissociated phoria was measured using the flashed Maddox rod technique. Vergence responses were stimulated from 4° symmetrical disparity vergence step stimuli. The peak velocity of the vergence response and the magnitude of the fusion initiating component (FIC) from an independent component analysis (ICA) were calculated. A linear regression analysis was conducted studying the vergence peak velocity as a function of the near dissociated phoria where the Pearson correlation coefficient was computed. Results: Before vergence therapy, the average with one standard deviation FIC magnitude of convergence responses from CI subjects was 0.29° ± 0.82 and significantly less than the FIC magnitude of 1.85° ± 0.84 for BNC (p < 0.02). A paired t-test reported that the FIC and near dissociated phoria before vergence therapy for CI subjects significantly increased to 1.49° ± 0.57 (p < 0.04) and became less exophoric to 3.5Δ ± 1.9 exo (p < 0.02) after vergence therapy. A significant correlation (r = 0.87; p < 0.01) was observed between the near dissociated phoria and the vergence ratio of convergence peak velocity divided by divergence peak velocity. Conclusion: The results have clinical translational impact in understanding the mechanism by which vergence therapy may be changing the vergence system leading to a sustained reduction in visual symptoms.